EXPLORATORY FISHING EXPERIMENTS IN HIRAKUD RESERVOIR -ORISSA STATE (1967-70) - GEORGE, V C; NAIDU, R M; KUNJfPALU, K K (Fishery Technology, 2016)
Suitable areas for fishing have been lccated in the middle and upper regions of the Mahanadi course of Hirakud reservoir. In the former the suitable period is during summer and beginning of monsoons, and in the latter in summer and winter months. The fishery of the reservoir is contributed by four species namely S. silo_ ndia, L. fimbriatus, C. mirgala and C. catla.